A FOUR-POINT EQUIVALENT METHOD OF THE BOLTED JOINTS STIFFNESS - LI YuanSheng; ZHANG GuangPeng; XIE FangFang; WANG LiYu (Jixie qiangdu)
Bolted joints is one of the most widely used fixing joints in machine tool structure,which directly affects the performance of the whole machine tool. In order to ensure the accuracy,the fine mesh is needed,which will result in a large scale of calculation and time consuming,using finite element analysis software to analyze the structure and performance of the whole machine tool. And so the exploration of simple and effective approach combining of the finite element model of machine tool bolted joints is of great significance. According to the experimental results,this paper obtains the characteristic parameters of the joint surface and the six stiffness of each element in the bolted joints is obtained by means of the analytical methods. And then,bolted joints of each element are replaced with the four equivalent springs of symmetric distribution in pairs and the calculation method of the equivalent spring stiffness ＆position is given on the basis of the principle of equivalent stiffness. In the finite element analysis of the whole machine tool,the equivalent spring unit is substituted for unit bolted joints and the solution of finite element model uses the equivalent stiffness of bolted joints by finite element model,which can greatly simplify the calculation of finite element model. The experimental results show that this method is feasible.